Human Capital Development Challenges During the COVID-19 Pandemic - Eva Nadya; Maryam Maryam; Filia Hanum; Kasmaniar Kasmaniar; Arsyad Arsyad (International Conference on Multidisciplinary Research, 2022)
The concept of human capital and strategic human resource management are critical to ensure success. Human capital is crucial to increase assets and give long-term advantages to both an enterprise and a country. However, the COVID-19 pandemic which began in early 2020 and still continues today is the reason behind the issues of health deterioration and low life expectancy rates. Similarly, the quality of learning suffered severe disturbance during the pandemic. As a result, this situation is critical for the overall development of human capital in Indonesia. The government's challenging task in the future is to develop a plan to ameliorate the situation in different affected areas such as health, education, and employment. This article examines various literature and supporting data that are relevant to the role of human capital in development in a country, current conditions, obstacles, achievements, and strategies that must be implemented in the framework of recovery from disruptions caused by the global economic crisis and the COVID-19 pandemic, both of which disrupted the overall economic order. This report also illustrates how Indonesia's situation improves human capital while also highlighting its successes. Keywords: Human Capital, Strategic Management, COVID-19 Pandemic, Human Development